Augmented Reality Media: Development and Validation to Improve Critical Thinking Skills of Elementary School Student - Miftakhul Khasanah; Ahmad Ipmawan Kharisma; Mochammad Miftachul Huda (Universitas Negeri Medan, 2025)
This study aims to determine the validity, practicality, and effectiveness of Augmented Reality media in improving the critical thinking skills of fourth-grade students in IPAS subjects in elementary schools. This study uses the Research and Development method with the ADDIE model, which has five stages, namely analyze, design, development, implementation, and evaluation. The study employed a Control Group Pretest-Posttest design with fourth-grade students at Muhammadiyah 1 Ngimbang Lamongan Elementary School. Data analysis was conducted through prerequisite tests and hypothesis testing. The results of the study indicate that: (1) The Augmented Reality learning media was found to be highly valid based on the validation results: media experts 3.80, design 3.84, content 3.86, and learning devices 3.80. (2) The media is considered practical based on student responses in small-group trials (3.46), large-group trials (3.57), and student activities (3.22 and 3.55). (3) The media is also effective, as evidenced by the T-test (0.000) and N-Gain scores of 40.62% (experimental class) and 68.09% (control class). It is concluded that Augmented Reality media can enhance elementary school students' critical thinking skills.